TEACHING EVERYDAY LIFE AND TRANSVERSAL SKILLS TO STUDENTS - Vazirakhon Rustamovna Ochilova (American Journals, 2022)
Self-care and practical life skills as they are taught in basic education are covered in this article. Examples and instructions on how to teach daily living skills and self-care are also provided. Transversal talents are more generic than subject-based competencies. It is preferable for everyday life skills and self-care to be taught as part of the curriculum if the development of these abilities is crucial for children and young people’s future and is a requirement for leading healthy and productive lives.
Keywords: Self-care, transversal talents, generic, emotional intelligence, practical decisions, qualities, abilities, and potential.